Respostas
respondido por:
14
A) √972 - √243 - √108.
~ simplificando
| | |
18√3 - 9√3 - 6√3 = (18-9-6) √3 =
= 3√3
~~》~~~~~~~~~》~~~~~~~~~~~》~~~~~~~~~~》
B) 3^√432 - 3^√128 + 3^√250
| | |
~ simplificando
6 (raiz cubica de √2) - 4 (raiz cúbica de √2) + 5 (raiz cúbica de √2)
> 6 3^√2 - 4 3^√2 + 5 3^√2
= (6-4+5)3^√2 === 7 (raiz cúbica de 2) > 7 3^√2
~ simplificando
| | |
18√3 - 9√3 - 6√3 = (18-9-6) √3 =
= 3√3
~~》~~~~~~~~~》~~~~~~~~~~~》~~~~~~~~~~》
B) 3^√432 - 3^√128 + 3^√250
| | |
~ simplificando
6 (raiz cubica de √2) - 4 (raiz cúbica de √2) + 5 (raiz cúbica de √2)
> 6 3^√2 - 4 3^√2 + 5 3^√2
= (6-4+5)3^√2 === 7 (raiz cúbica de 2) > 7 3^√2
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás